SAP NetWeaver portal technology [ the complete reference - Jay, Rabi (McGraw-Hill, 2008)
Offers details on implementing and managing a SAP Portal, the tool that can integrate content - websites, applications, legacy systems, databases and document directories - into one accessible interface. This work covers the lifecycle of portal implementation, from planning, designing, and installing to configuring, tuning, and security